PENGARUH KEJELASAN SASARAN ANGGARAN, SISTEM PELAPORAN, KOMPETENSI TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DIMEDIASI OLEH KOMITMEN ORGANISASI (Studi Pada Organisasi Perangkat Daerah Kabupaten Kampar) - Khairunsyah, Khairunsyah; Efni, Yulia (Jurnal Tepak Manajemen Bisnis, 2018)
The Purpose of this study was to examine the influence clarity budgetarytargets, reporting systems, competency to performance accountability of governmentinstitution through organizational commitment as an intervening variable, specificallyinstitution of Kampar district. Respondents in this study are the civil servants whoserved as head of finance, program and evaluation, staff in 20 OPD of Kampar district.The amount of samples in this research was 80 respondents. The sample collectionmethod using proportional stratified sampling, while the method of processing datausing Partial Least Square. Result of this study indicates that clarity budgetary targets,competency, organizational commitment have significant effects on performanceaccountability of government institution, in otherhand, reporting systems doesnât havesignificant effect. Clarity budgetary targets and competency to the performanceaccountability of the government institution through organizational commitment as anintervening variable have significant effects.